Evaluation of Vancomycin Population Susceptibility Analysis Profile as a Predictor of Outcomes for Patients with Infective Endocarditis Due to Methicillin-Resistant Staphylococcus aureus - Casapao, Anthony M. (American Society for Microbiology, 2014)
Infective endocarditis due to methicillin-resistant Staphylococcus aureus (MRSA IE) is associated with high morbidity and mortality. Vancomycin continues to be the primary treatment for this disease. The emergence of heterogeneous vancomycin-intermediate Staphylococcus aureus (hVISA), defined as a modified population analysis profile (PAP) of ≥0.9, may affect patient outcomes. The objective of this study was to evaluate the relationship of vancomycin subpopulation susceptibility and the clinical outcomes of MRSA IE. We conducted a retrospective cohort study of patients treated with vancomycin for MRSA IE from 2002 to 2013 at the Detroit Medical Center. A modified PAP was used to measure the vancomycin PAP MIC and the PAP-to-area under the curve (AUC) ratio. Treatment failure was defined as bacteremia for ≥7 days or death attributed to MRSA. Classification and regression tree (CART) analysis was used to select a failure breakpoint between the PAP-AUC ratios and the PAP MIC. A total of 202 patients were included in the study. Twenty-seven percent of the patients had left-sided IE, 19% of the strains were hVISA, and 70% of the strains were staphylococcal cassette chromosome mec element (SCCmec) type IV. Overall treatment failure was observed in 64%; 59% had persistent bacteremia, and the 30-day attributable mortality rate was 21%. The CART breakpoint between failure and success in terms of the PAP-AUC ratio was 0.9035. On logistic regression analysis, intensive care unit (ICU) admission (adjusted odds ratio [aOR], 2.8; 95% confidence interval [CI], 1.5 to 5.2) and a PAP MIC of ≥4 mg/liter (aOR, 3.2; 95% CI, 1.3 to 8.4) were associated with failure (P = 0.001 and 0.015, respectively). A PAP MIC of ≥4 mg/liter and ICU admission were significant for treatment failure for patients with MRSA IE. The PAP-AUC ratio of ≥0.9035 predicted failure consistent with the hVISA definition. The role of population MIC analysis in predicting outcome with MRSA infections warrants further investigation.